Analysis of the Implementation of Elderly-Friendly Digital Services in Facilitating Access to Information and Disbursement of Pension Funds at PT Perkebunan Nusantara III (Persero) - Charos, Wanda Aprilly; Suhairi (International Humanity Advance, Business & Sciences, 2025)
This study examines the implementation of elderly-friendly digital services in facilitating access to information and disbursement of pension funds at PT Perkebunan Nusantara III (Persero). Through a qualitative approach with observation, interview, and document analysis methods, the study revealed that the Dapenbun Online application has had a positive impact on operational efficiency and transparency, but still faces a number of significant challenges. The main problems include high manual error rates, less user-friendly interface design, technical authentication constraints, and limited digital infrastructure in remote areas. The study recommends strategic solutions such as increasing automation using machine learning, redesigning the interface, developing alternative authentication features, and strengthening digital education programs to create a more inclusive and effective system for retirees